The reliability of Juvenile Arthritis Magnetic Resonance Imaging Scoring system in the evaluation of the shoulder joint in juvenile idiopathic arthritis - Murugan Sudhakar; Shivani Deswal; Namrita Sachdev; Somdipa Pal; Tribhuvan Pal Yadav (Archives of Rheumatology, 2022)
Objectives: We aimed to evaluate shoulder joint by magnetic resonance imaging (MRI) using the Juvenile Arthritis Magnetic Resonance Imaging Scoring (JAMRIS) system in children with juvenile idiopathic arthritis (JIA) and to compare clinical, laboratory parameters and disease activity scores with MRI parameters. Patients and methods: A total of 32 shoulder joints of 20 patients (16 males, 4 females; mean age: 8.9±3.5 years; range, 2.5 to 14 years) with a known diagnosis of JIA and a clinical suspicion of shoulder joint involvement and underwent MRI were included. Reliability was determined by inter- and intra-observer correlation coefficients. Correlation of the clinical and laboratory parameters with JAMRIS scores was done using the non-parametric tests. Sensitivity of clinical examination to detect shoulder joint arthritis was also determined. Results: Of the 32 joints, 27 joints in 17 patients showed MRI changes. Seven joints in five patients fulfilled the definition of clinical arthritis, all revealed MRI changes. In 25 joints without clinical arthritis, early and late MRI changes were seen in 19 (67%) and 12 (48%) joints, respectively. The inter- and intra-observer correlation coefficients for JAMRIS system were excellent. No correlation was found between MRI parameters, clinical, laboratory, and disease activity scores. The sensitivity of clinical examination to detect shoulder joint arthritis was 25.9%. Conclusion: The JAMRIS system is reliable and reproducible to determine shoulder joint inflammation in JIA. Detection of shoulder joint arthritis by clinical examination has a poor sensitivity